Terahertz and Raman Spectroscopic Investigation of Monohydrate Cocrystal of Antitubercular Isoniazid with Protocatechuic Acid - Yanhua Bo; Jiyuan Fang; Ziming Zhang; Jiadan Xue; Jianjun Liu; Zhi Hong; Yong Du (Pharmaceutics, 2021)
Pharmaceutical cocrystal provides an alternative modification strategy for the formulation development of drugs owning to their potential ability to improve the physicochemical properties of active pharmaceutical ingredients (APIs) efficiently by changing inter-molecular interactions between raw materials. Isoniazid (INH) is an indispensable main drug for the treatment of tuberculosis, but its tablet formulation is unstable and prone to degradation. In the present study, the monohydrate cocrystal of INH and protocatechuic acid (PA) was prepared by solvent evaporation using PA as cocrystal former to optimize the properties of INH. The parent materials and corresponding 1:1 molar ratio INH-PA monohydrate cocrystal have been characterized by the terahertz time-domain (THz-TDS) and Raman spectroscopy. The THz absorption spectra displayed that there were obvious differences between the peaks of experimental cocrystal and the parent materials, and the same situation was found in Raman vibrational spectra. In addition, density functional theory (DFT) was applied to simulating and optimizing the structure of INH-PA monohydrate cocrystal and supplied corresponding vibrational modes. Our results provided a unique method to characterize the formation of INH-PA monohydrate cocrystal at the molecular-level and a lot of information about cocrystal structure and intra-molecular and/or inter-molecular hydrogen bond interactions in the emerging pharmaceutical cocrystal fields.